Simulation Model of PID Controller for DC Servo Motor at Variable and Constant Speed by Using MATLAB - Abdullah, Zainab B.; Shneen, Salam Waley; Dakheel, Hashmia S. (Journal of Robotics and Control (JRC), 2023)
The current simulation is conducted in order to develop an appropriate design for the control systems and control the speed of the electric motor. To obtain the appropriate and required design, work is carried out for two cases, a constant speed and the other case at variable speed in different conditions for operation of dc servo motor, these conditions include rotating in a clockwise direction, break and returns rotating in the opposite clockwise direction. Through the proposed working conditions, it is possible to obtain the best values for the parameters of the control unit that improve the working performance of dc servo motor, which were shown by the simulation results and their values were kp =5, ki=3 and kd=5 for PID controller. Which changed the system response speed, rise time and the upper and lower bypass ratio at acceptable rates and ratios to prove an improvement procedure in the work of the electric motor.